Legong Krincing Suara - Ni Kadek Intan Pramudita Dewi; I Wayan Sutirtha; I Putu Bagus Bang Sada Graha Saputra (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2025)
Legong Krincing Suara The Legong Krincing Suara dance is a new Legong dance creation with Gongseng as the creative source of creation. The stylist tries to combine aspects of movement, music, make-up and fashion, namely Legong and Gongseng. The creation of the Legong Krincing Suara dance uses the Panca Sthiti Ngawi Sani creation method created by Prof. Dr. I Wayan Dibia, SST, MA. Which include: Ngawirasa, Ngawacak, Ngaplan, Ngawangun, and Ngebah. This dance is performed in a group using 6 female dancers with a dance structure, part 1 depicts the sound of gongseng like a